Community, Conflict and the State - Cooper, C. author. aut Link
VIII, 264 p.
Keywords: Community safety is a narrowly defined concept that allows states to ignore arguably more serious threats caused by pro-market policies and the actions of major corporations. This book redresses the idea of what constitutes a social harm and outlines a new policy agenda.